Blogging and citizenship: The Malaysian experience - Mohamed, Shafizan (Penerbit Akademia Baru, 2017)
This study explicates the relationship between media and citizenship through the experiences of the Malaysian bloggers. The theoretical idea of Citizen’s Media explains and makes sense of this relationship. The areas of focus are: (1) the blogging experience, (2) the types of blog, and (3) representation of citizenship. A purposive sample of 30 Malaysian bloggers was interviewed during a three-months period. The study identified two types of bloggers: The Activist and the Diarist. While the two blogger categories have contrasting characteristics, they are not entirely opposites. A detailed look into the bloggers’ motivation, style, practices and rewards reveal that the experience of citizenship is very much evident in both blogging categories.